Amino acid profile, pasting, and sensory properties of croissant snacks produced from wheat‐fermented Bambara flour. Issue 4 (9th July 2020) - Arise, Abimbola K.; Taiwo, Ganiyat O.; Malomo, Sunday A.
Abstract: Croissants are wheat flour‐based delicious bakery products that are usually consumed as part of breakfast or lunch meals. In this study, fermented bambara groundnut was used to supplement wheat flour in the following ratios (5:95%; 10:90%; 15:85%; 20:80%, and 25:75%, respectively) to produce croissant snacks. The results of the functional properties of the flour blends revealed an increase in water absorption capacity (81–92%) and bulk densities (0.81–1.20 g/cm 3 ) with an increased added ratio of fermented Bambara flour. Contrarily, increasing the Bambara groundnut in the blend resulted in the decreased oil absorption capacity (70–63%) and the swelling capacity (0.75–0.4%). The pasting characteristics data revealed an increase in pasting temperature and setback viscosity and a decrease in peak, breakdown, and final viscosities, as well as trough and peak time with an increase in the addition of fermented Bambara flour. Proximate composition of the croissant showed an increase in protein, fiber, ash, moisture, and fat content and a decrease in carbohydrate content. Physical properties data showed an increase in loaf weight but a decrease in loaf volume and specific volume of the snacks. The amino acid profile showed an increase in the amount of essential amino acids in the enriched croissants (28.66/100 g protein) compared with the control sample (24.05/100 g protein). The sensory attributes obtained for the croissants showed that the products were highly acceptable by the panelists. Hence, the affirmation that the acceptable quality and high nutritional croissants could be produced from wheat‐fermented Bambara groundnut flour blends.